Mollusca collected by Agassiz trawl from the 2016 SO-AntEco (JR15005) expedition to the South Orkney Islands, Antarctica - data - Jan Steger; Katrin Linse; Yi-Ming Gan; Huw Griffiths (Biodiversity Data Journal, 2023)
This dataset contributes to the knowledge of macro- and megafaunal Mollusca associated with a range of benthic habitat types in the South Orkney Islands, Antarctica, an exceptionally diverse region of the Southern Ocean. The information presented is derived from Agassiz trawl samples collected on the archipelago’s shelf plateau and slope, within and outside of the South Orkney Islands Southern Shelf Marine Protected Area (SOISS MPA). Sampling was conducted in the framework of the British Antarctic Survey/SCAR “South Orkneys - State of the Antarctic Ecosystem” (SO-AntEco) project aboard RRS James Clark Ross during expedition JR15005 in Austral summer 2016. This dataset is published by the British Antarctic Survey under the licence CC-BY 4.0. We would appreciate it if you could follow the guidelines from the SCAR Data Policy (SCAR 2023) when using the data. If you have any questions regarding this dataset, do not hesitate to contact us via the contact information provided in the metadata or via data-biodiversity-aq@naturalsciences.be. Issues with the dataset can be reported at https://github.com/biodiversity-aq/data-publication/. This dataset is part of the Biodiversity, Evolution and Adaptation Project of the Environmental Change and Evolution Program of the British Antarctic Survey. The cruise report of the expedition is available at https://www.bodc.ac.uk/resources/inventories/cruise_inventory/reports/jr15005.pdf.We report occurrences of Mollusca from individual samples taken with a 2 m-wide Agassiz trawl (AGT) in the framework of the February – March 2016 research expedition JR15005 of RRS James Clark Ross to the SOISS MPA and adjacent shelf and slope areas. Of 78 successful AGT deployments, 44 trawls at depths ranging from 235-2194 m yielded living Mollusca, totalling 2276 individuals, 67 morphospecies and 163 distributional records. One hundred and fifteen empty shells were also collected and recorded in the dataset. Three morphospecies (one Bivalvia and two Gastropoda) were sampled exclusively as empty shells, yielding a total of 70 morphospecies and 2391 specimens represented in the dataset. All specimens were preserved in 96% undenatured ethanol and are stored as vouchers in the collections of the British Antarctic Survey (BAS), Cambridge, United Kingdom. The publication of this dataset aims at increasing the knowledge on the biodiversity, abundance and geographical and bathymetric distribution of larger-sized epi- and shallow infaunal Mollusca of the South Orkney Islands.